Cochlear implant in patients with incomplete partition type II: surgical considerations - Takhellambam, Biram Singh; Venkataramani, Nithya; Natarajan, Kiran; Lairellakpam, Umalakshmi; Kumari, Abha; Arumugam, Senthil Vadivu; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: This study presents our experience on surgical aspects, complications and outcome of cochlear implants in incomplete partition type II patients. Methods: 7 children in the age group of 1 to 5 years with incomplete partition type II, 5 females and 2 males were studied retrospectively from the database of tertiary care centre from February 2015 to December 2016. Results: 5 patients had conventional transmastoid facial recess approach of which one patient had removal of incudal buttress, incus and stapes suprastructure to facilitate middle turn cochleostomy. 2 patients had subtotal petrosectomy. Complete insertion of electrode was achieved in all patients; by middle turn cochleostomy in 1 patient, cochleostomy in another patient, extended round window in 3 patients and round window in 2 patients. Med-el Synchrony + Form 19 were used in all patients and complete insertion was achieved in all. 4 patients had CSF leak which was sealed with soft tissue. One patient had device failure. 5 children show improvement in CAP and SIR score. One had device failure and was subsequently explanted and re-implanted. Conclusions: Cochlear implantation in patients with incomplete partition type II is challenging and thorough knowledge of anatomy is essential. One must be competent enough to expedite different surgical approaches and manage the associated complications. Prior counselling for guarded outcome and eventualities are necessary in such patients.